A Multicentre Based Observation of a Screening tool to Differentiate Microcytosis and Hypochromia (Anwer Khan Modern Medical College Journal, 2017)
Back ground: Iron deficiency anemia (IDA) and beta-thalassaemia trait (B-TT) are the most common causes of hypochromic microcytic anemia. Many indices have been defined to quickly discriminate these similar entities via parameters obtained from automated blood count analyzers.Methodology: The purpose of the study was to evaluate the predictive value of these indices in differential diagnosis of IDA and B-TT in adult cases. In this study we use auto-analyzer based formula of percentages of microcytic and hypochromic red cells (M/H ratio=% of Microcytosis/% of Hypochromia) as a screening tool for thalassaemia trait in Bangladeshi population.Results: A total of 150 subjects w ere included in this study with 50 known obligate carrier of beta-thalassaemia trait and 100 patients with hypochromia and microcytosis. Confirmatory tests for IDA were performed if serum ferritin level was 3.5% , on agarose gel Haemoglobin electrophoresis at an alkaline pH (8.6) where, in addition, MCV